Trends of Doctoral Dissertations that have been Defended at Specialized Academic Council of the Main Astronomical Observatory of the NAS of Ukraine in 1991-2016 - Vasilyeva, I.E. (Science and Innovation, 2024)
The research is aimed at revealing trends and estimating quality of doctoral dissertations that have been defended at Specialized Academic Council of the Main Astronomical Observatory of the NAS of Ukraine within the period from 1991 to 2016. The analysis has shown a drop in the number of defended dissertations per year, which is consistent with the general downward trend in the number of employees in the R&D of Ukraine, as well as a rise in the average age of doctoral degree seekers. However, during this period, the share of women who have defended their doctoral dissertation increased significantly. The citation rate of doctoral researchers and their average h-index have remained constant. Overall, the quality of doctoral dissertations which have been defended at the Main Astronomical Observatory remains high throughout the period of Ukraine’s independence.